Pelatihan Penggunaan Alat Penghalus Kotoran Ternak di Kelompok Ternak Sidomaju Bantul Yogyakarta - Indarjulianto, Soedarmanto; Widiyono, Irkham; Sarmin, Sarmin; Airin, Claude Mona (IGKOJEI: Jurnal Pengabdian Masyarakat, 2021)
ABSTRACT The utilization of manure as organic fertilizer is on the rise, but the coarse form may negatively impact the aesthetics. This community service aims to train the farmers to operate the livestock manure grinder machine. The community service was performed in the Sidomaju livestock group, Panggungharjo village, Sewon, Bantul, Yogyakarta, with 37 farmers. The method for this community service is providing online presentations followed by online and offline workshops. The participation and satisfaction of the participants were measured by direct interaction and analyzed descriptively. The results of this community service showed that all farmers were more enthusiastic to participate in offline activities rather than online ones. All of the participants of the training can operate the livestock manure grinder machine. Based on the results of this activity, it is concluded that the training on the use of grinders for livestock manure machine has been adopted by farmers. Keywords: Manure; Manure grinder; Livestock; Organic manure ABSTRAK Pemanfaatan kotoran ternak sebagai pupuk organik semakin meningkat, tetapi bentuk yang kasar dapat mengurangi estetika. Pengabdian kepada masyarakat ini bertujuan melaksanakan pelatihan penggunaan alat pelembut kotoran ternak. Pengabdian dilakukan di kelompok ternak Sidomaju, desa Panggungharjo, Sewon, Bantul, Yogyakarta yang beranggotakan 37 peternak. Metode kegiatan yang dilakukan adalah dengan presentasi dan pelatihan secara daring dan luring. Keterlibatan dan kepuasan peserta diukur melalui interaksi langsung dan hasilnya dianalisis secara deskriptif. Hasil pengabdian menunjukkan bahwa semua peternak lebih antusias mengikuti kegiatan secara luring. Semua peserta yang hadir dalam pelatihan telah dapat mengoperasionalkan mesin penghalus kotoran ternak. Berdasar hasil kegiatan ini, disimpulkan bahwa pelatihan penggunaan mesin penghalus kotoran ternak telah dapat diadopsi oleh peternak. Kata kunci: Kotoran ternak; Pelembut kotoran; Pupuk organik; Ternak